Desert Microbes for Boosting Sustainable Agriculture in Extreme Environments - Alsharif, Wiam; Saad, Maged M.; Hirt, Heribert (Frontiers in Microbiology, 2020)
A large portion of the earth’s surface consists of arid, semi-arid and hyper-arid lands. Life in these regions is profoundly challenged by harsh environmental conditions of water limitation, high levels of solar radiation and temperature fluctuations, along with soil salinity and nutrient deficiency, which have serious consequences on plant growth and survival. In recent years, plants that grow in such extreme environments and their naturally associated beneficial microbes have attracted increased interest. The rhizosphere, rhizosheath, endosphere, and phyllosphere of desert plants display a perfect niche for isolating novel microbes. They are well adapted to extreme environments and offer an unexploited reservoir for bio-fertilizers and bio-control agents against a wide range of abiotic and biotic stresses that endanger diverse agricultural ecosystems. Their properties can be used to improve soil fertility, increase plant tolerance to various environmental stresses and crop productivity as well as benefit human health and provide enough food for a growing human population in an environment-friendly manner. Several initiatives were launched to discover the possibility of using beneficial microbes. In this review, we will be describing the efforts to explore the bacterial diversity associated with desert plants in the arid, semi-arid, and hyper-arid regions, highlighting the latest discoveries and applications of plant growth promoting bacteria from the most studied deserts around the world.